From Playground to Boardroom: Endowed Social Status and Managerial Performance - Du, Fangfang (Journal of Financial and Quantitative Analysis, 2022)
Using U.S. census survey data on CEOs’ residence in their formative years, I document a negative relation between CEOs’ endowed family wealth and managerial performance. Consistent with the view that CEOs born into low-income families face higher entry barriers but may possess greater levels of ability that enable them to become CEOs, I find that CEOs born into less privileged families outperform those from higher-wealth families. The outperformance of CEOs from less wealthy families is not driven by risk taking or omitted variables. Overall, my results suggest that CEOs’ social endowment provides a useful signal for their managerial ability.